Towards a research agenda about the relationship between social capital and tourism - González Damián, Alfonso; Ramírez Hernández, O. Ismael; Rosado Varela, A. Aarón (Agricultura, Sociedad y Desarrollo, 2022)
The present study conducts a reflective analysis of academic production about the relationship between tourism and social capital, with the aim of responding to the question: What are the themes, variables and paths that the study of social capital ought to follow in the tourism sphere? It became clear that although there is relevant academic production regarding the relationship between tourism and social capital, the entire range of the possibilities for its study and understanding has still not been covered, which in addition limits its academic knowledge, the possibility of designing intervention actions that could have an impact on the improvement of tourism or of social capital in societies where they participate, or in both. The elements to be considered when approaching a research agenda are presented, in order to delve into the knowledge of the relationship between tourism and social capital as theoretical-conceptual framework, that is, stemming from the type of relationship between the themes, the scenarios to be considered, the scales to approach the studies, the actors to be included, and the dimensions, categories, themes or variables to be considered. Finally, reflections are made about what has been researched until today, and the different scientific academic work lines that can be pursued in the future.